The Massuru' Tondok Ritual as a Space for Encountering the Transcendent: An Analysis Based on the Thought of Ninian Smart - Agustinus Abraham (Intellektika : Jurnal Ilmiah Mahasiswa, 2026)
This study examines the Massuru’ Tondok ritual as a space for encountering the Transcendent within the Aluk Todolo belief system of the Torajan community in the villages of Suppiran, Mesakada, and Salisali (SMS), Pinrang Regency, South Sulawesi. The ritual is understood not merely as a cultural tradition, but also as a religious expression through which the community establishes a relationship with Puang Matua as the Supreme Being. This research employs a qualitative method using a literature review approach. The analysis is based on Ninian Smart’s theory of the dimensions of religion, particularly the doctrinal, mythological, ritual, experiential, ethical, social, and material dimensions. The findings reveal that Massuru’ Tondok contains interconnected religious elements manifested through myths, ritual symbols, sacrificial offerings, prayers, customary regulations, communal participation, and sacred material objects. The ritual functions as a medium for expressing gratitude, seeking protection, fertility, and prosperity, while also strengthening social solidarity and maintaining harmony between humanity, nature, and the Divine. Therefore, this study concludes that Massuru’ Tondok represents a living religious and cultural heritage that continues to hold deep spiritual and social significance for the Aluk Todolo community.